Differences in the clinical and radiological characteristics of lunginvolved toxocariasis between toxocariasis with eosinophilia and those without eosinophilia - Park, Bo Mi; Jeong, Sang Ok; Park, Hee Sun; Jung, Sung Soo; Kim, Sun Young; Kim, Ju Ock; Lee, Jeong Eun (Journal of Thoracic Disease, 2014)
Background: Previously, most studies did not discuss about the characteristics of lung-involved toxocariasis without eosinophilia. However, the patients are not always accompanied by eosinophilia, so it is necessary to learn about the clinical and radiologic features that may predict pulmonary toxocariasis without eosinophilia. In addition, we also want to check the differences in characteristics between the two groups based on the presence of eosinophilia. Methods: We investigated patients from October 2009 to February 2014 with antibody against Toxocara positive using enzyme-linked immunosorbent assay (ELISA), abnormal chest X-ray, and computed tomography (CT) findings. This retrospective study included patients diagnosed as toxocariasis with pulmonary involvement, using the results of laboratory findings, symptoms, and CT at the time of diagnosis. Results: Out of 88 patients, 78% were male and 22% were female; and the mean age was 51 years. The mean eosinophil fraction in peripheral blood was 11.8%. The most common chest CT findings of patients with eosinophilia were nodules plus ground glass opacity (GGO) pattern, and nodules were found in patients with no eosinophilia. Pure GGO was the most common predominant subtype in GGO lesions of patients with eosinophilia. In terms of anatomical distribution, random distribution was seen more in patients with eosinophilia than those without eosinophilia, with statistically significance (P=0.042). In patients who underwent additional CT scans, 44% of those with eosinophilia had migrating lesions and had significant differences from patients without eosinophilia (P=0.008). Conclusions: There were no significant differences in lesion characteristics with the exception of random anatomic distribution between patients with and without eosinophilia. However, there was a significant difference between the fixation and migration of the lesion in patients with and without eosinophilia.